Effects of physical exertion on trans-tibial prosthesis users' ability to accommodate alignment perturbations. (February 2016) - Fiedler, Goeran; Slavens, Brooke A; O'Connor, Kristian M; Smith, Roger O; Hafner, Brian J
Background: It has long been reported that a range of prosthesis alignments is acceptable in trans-tibial prosthetics. This range was shown to be smaller when walking on uneven surfaces. It has also been argued that findings on gait with prostheses that were obtained under laboratory conditions are limited in their applicability to real-life environments. Objectives: This study investigated the hypothesis that efforts to compensate for suboptimal alignments by active users of trans-tibial prostheses become less effective when levels of physical exertion increase. Study design: A 2 × 2 repeated-measures analysis of variance was conducted to compare the effects of physical exertion and subtle alignment perturbations on gait with trans-tibial prostheses. Methods: The gait of eight subjects with trans-tibial amputation was analyzed when walking with two different prosthesis alignments and two different physical exertion levels. The main and interaction effects were statistically evaluated. Results: Bilateral step length symmetry and measures of step variability within the same leg were found to be affected by the intervention. There was no significant effect on index variables that combined kinematic or kinetic measures. Conclusion: Findings showed that persons with trans-tibial prostheses responded heterogeneously to the interventions. For most variables, the research hypothesis could not be confirmed. Clinical relevance: Findings support the practice of allotting several sessions to the alignment of trans-tibial prostheses, as users' gait responds differently to perturbations when external factors (e.g. exertion) change. Furthermore, the found inhomogeneity in the population of persons with trans-tibial amputation supports the use of technical gait assessment methods in clinical practice.